A theoretical and empirical investigation into investment activities of technologically-intensive Chinese state-owned enterprises in the UK. Issue 1 (February 2021) - Vukicevic, Jelena; Fallon, Grahame; Ott, Ursula F.
Highlights: Chinese state-owned enterprises intend to become world leaders by identifying technology gaps and tapping into technological networks. To achieve this they are acquiring existing technology and more importantly developing new technology. Permanent R&D bases in the UK are being set up to achieve a global integrated network. Government influence is evident at strategy level and divergent management practices are leading to an adaptable mindset. There are more management styles possible than the usual top-down style, through adaptation to different management practices. Abstract: This paper examines the determinants of direct investment in the UK by technology-intensive Chinese state-owned enterprises (SOEs). It also investigates the ways in which investment strategies are being employed for entry to the UK and to achieve access to technology. Drawing on an inductive case study strategy it is found that Chinese SOEs are motivated by their ambitions to close the technology gap by tapping into UK knowledge networks. In terms of entry strategies, the findings indicate that the initial focus on existing technology subsequently shifts to the creation of added R&D capacity and new technology. This is achieved from a permanent UK R&D base which is integrated into the parent companies' wider R&D networks. Technology creation is enabled by adoption of divergent management practices, especially at operational level, reflecting the parent companies' surprisingly adaptable mindsets.